Biased perceptions of income distribution and preferences for redistribution: Evidence from a survey experiment - Cruces, Guillermo Antonio (2013)
Individual perceptions of income distribution play a vital role in political economy and public finance models, yet there is little evidence regarding their origins or accuracy. This study examines how individuals form these perceptions and explores their potential impact on preferences for redistribution. A tailored household survey provides original evidence on systematic biases in individuals' evaluations of their own relative position in the income distribution. The study discusses one of the mechanisms that may generate such biases, based on the extrapolation of information from endogenous reference groups, and presents some suggestive evidence that this mechanism has significant explanatory power. The impact of these biased perceptions on attitudes toward redistributive policies is studied by means of an experimental design that was incorporated into the survey, which provided consistent information on the own-ranking within the income distribution to a randomly selected group of respondents. The evidence suggests that those who had overestimated their relative position and thought that they were relatively richer than they were tend to demand higher levels of redistribution when informed of their true ranking.